Drug trafficking in the Golden Triangle: The Myanmar problem and ASEAN effectiveness - Nathan Harper; Nathan Tempra (Kelompok Studi Mahasiswa Pengkaji Masalah Internasional Unpar, 2019)
This essay explores the issue of drug trafficking and production in Myanmar to understand the extent of damage this problematic situation has on the South East Asian region and to discuss what steps are being taken by institutions to stem the proliferation of narcotics such as heroin and amphetamines. Myanmar’s turbulent political history and unique geographical position have been explained to garner knowledge on why drug trafficking and production are so closely associated with the nation. The policymaking efforts of the Association of South East Asian Nations (ASEAN) to combat drug trafficking and production in the region have so far been plagued by obstructions such as internal corruption, a lack of multilateral cooperation and insufficient resources. These barriers combine to create policy that it is aligned closer to empty rhetoric than actual physical implementation. The ASEAN and China Cooperative Operations in Response to Dangerous Drugs (ACCORD) agreement has shown signs of a changing tide toward effective policymaking, due mainly to China stepping up to the plate of regional leadership. This essay recommends that in order to successfully fight drug trafficking and production, ASEAN need to establish more realistic and achievable goals with an emphasis on rehabilitation rather than punishment. Furthermore, compliance mechanisms should be put in place by ASEAN so that countries such as Myanmar, who often deviate from the status quo of drug policy, will be reprimanded for doing so in the future. Thus, creating an environment of multilateral cooperation, togetherness and consistency in relation to combatting the illegal drug trafficking and production trade